Criminal Liability For The Elements Of Embezzlement And Fraud In A Rotating Savings Organizer’s Payment Default Case (A Case Study at H&P Advocates in Surakarta) - Helen Stevienka; Triana Kurniawati; Sulviana Febiyanti; Dian Utami; Rahmad Kurniawan; Yoseph Rafael Sinaga; Puspaningrum (Asosiasi Dosen Muda Indonesia, 2026)
The phenomenon of arisan as a trust-based fund-raising mechanism is widespread in society, but its practice is prone to abuse through manipulative schemes that result in collective losses. This study aims to analyse the forms of criminal liability for perpetrators of arisan default by examining the fulfilment of the elements of criminal fraud and embezzlement. The research method uses a normative juridical approach supported by empirical data from case handling at law firms. The results show that a series of tricks, unauthorised control of funds, and failure to fulfil payment obligations indicate the cumulative fulfilment of the elements of Article 486 and Article 492 of the Criminal Code. Criminal liability is imposed on the perpetrator based on the offence of intent with the aim of obtaining unlawful gains. This study confirms that failure to pay arisan, preceded by the manipulation of trust, is not merely a civil breach of contract, but a criminal act.